PROTOTYPE OF MANAGEMENT INFORMATION SYSTEM FOR OFFICIAL TRAVEL ORDERS (SPPD) AND ASSIGNMENT ORDERS (SPT) OF THE SECRETARIAT OF THE CITY LEGISLATIVE COUNCIL OF BENGKULU - Witriyono, Harry; Fauzi, M. Ikhwan; Kms. M. Yeri Habibullah; Muhammad Ariq Shidqy; Mohammad Abkar Nur Rohman (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Prototype of Travel Orders Management Information System (TOMIS) for the Secretariat of the Regional People's Representative Council (DPRD) of Bengkulu City is an innovation aimed at enhancing efficiency and effectiveness in the administration of official travels and assignments within the Secretariat of the DPRD of Bengkulu City. This article discusses the steps involved in the creation and development of the prototype information system, starting from needs analysis, data management, to implementation. The development method employed is prototyping, which allows users to provide feedback and observe the system's progress firsthand. The prototype is designed to address various issues commonly encountered in the administrative processes of official travels and assignments, such as difficulties in submitting Travel Orders (SPPD) and Assignment Orders (SPT), as well as inefficient monitoring, evaluation, and filing procedures. With the existence of this prototype, it is anticipated that the administrative processes of official travels and assignments within the Secretariat of the DPRD of Bengkulu City will become more structured, transparent, and efficient. Furthermore, this prototype can serve as a reference for other institutions in developing similar information systems.